Effectiveness of two thermal activated orthodontic archwire sequences based on transition temperature range during alignment: A randomized non-controlled comparative study - Gurgel, Julio de Araujo [UNESP]; Maio Pinzan-Vercelino, Celia Regina; Ferreira, Meire Coelho; Silva, Daniella de Oliveira da; Flores-Mir, Carlos; Schwartz, Edson Albano (Elsevier B.V., 2020)
Introduction > It has been suggested that heat-activated NiTi archwires (HANT) speed up crowding alleviation. HANT wires are available with different austenite finish temperatures. Objective > The aim of the present study was to compare the effectiveness of two alignment sequences using thermally activated archwires with different austenite activation temperatures for the correction of mandibular anterior crowding. Material and methods > The following NiTi archwire sequence was used for both groups: 0.012 in (conventional NiTi), 0.018 in (heat-activated NiTi archwires), 0.016 x 0.022 in (heat-activated NiTi archwires) and 0.019 x 0.025 in (conventional NiTi). The conventional NiTi used for both groups belongs to the same commercial brand. Two different austenite activation temperatures (35 degrees C and 37 degrees C) were used for the heat-activated archwires. The primary outcome was the degree of crowding correction measured on study models. The secondary outcome was crowding survival time over a six-month period. This RTC included fifty-four patients that were randomly allocated to the two different archwire sequences. A Mann-Whitney test was used to compare the groups regarding crowding alleviation. A survival curve was created using the Kaplan-Meier method to illustrate the reduction of crowding over time. A Mantel-Cox log-rank test was used to compare survival times (until correction of crowding). Results > No differences in crowding alleviation were identified between both groups (log-rank test; P = 0.77). Conclusions > The two alignment sequences with different thermal activated archwires at 35 degrees C and 37 degrees C achieved similar clinical results during the correction of mandibular anterior crowding.
Keywords: Wire; Aligning archwire; Copper-nickel-titanium; Orthodontic wires; Transition phase; Temperature